The effect of fish oil enema in ethanol induces colonic damage in rats - Hakan YÜCEYAR,; Ömer ÖZÜTEMİZ,; A. HÜSEYİNOV,; Murat ALKANAT,; Serhat BOR,; Çiğdem DİNÇER,; Ahmet ÇOKER,; Yücel BATUR, (Turkish Journal of Gastroenterology, 2019)
-